The first symbiont-free genome sequence of marine red alga, Susabi-nori (Pyropia yezoensis). - Yoji Nakamura (Public Library of Science (PLoS), 2013)
Nori, a marine red alga, is one of the most profitable mariculture crops in the world. However, the biological properties of this macroalga are poorly understood at the molecular level. In this study, we determined the draft genome sequence of susabi-nori (Pyropia yezoensis) using next-generation sequencing platforms. For sequencing, thalli of P. yezoensis were washed to remove bacteria attached on the cell surface and enzymatically prepared as purified protoplasts. The assembled contig size of the P. yezoensis nuclear genome was approximately 43 megabases (Mb), which is an order of magnitude smaller than the previously estimated genome size. A total of 10,327 gene models were predicted and about 60% of the genes validated lack introns and the other genes have shorter introns compared to large-genome algae, which is consistent with the compact size of the P. yezoensis genome. A sequence homology search showed that 3,611 genes (35%) are functionally unknown and only 2,069 gene groups are in common with those of the unicellular red alga, Cyanidioschyzon merolae. As color trait determinants of red algae, light-harvesting genes involved in the phycobilisome were predicted from the P. yezoensis nuclear genome. In particular, we found a second homolog of phycobilisome-degradation gene, which is usually chloroplast-encoded, possibly providing a novel target for color fading of susabi-nori in aquaculture. These findings shed light on unexplained features of macroalgal genes and genomes, and suggest that the genome of P. yezoensis is a promising model genome of marine red algae.